Effect of FDR, NPF and Inflation on the Profitability of Bank BNI Syariah - Zia Firdaus Nuzula (Universitas Islam Negeri (UIN) Walisongo Semarang, 2020)
Purpose - This study aims to determine the effect of the amount of financing, financing problems and inflation on the profitability of Bank BNI Syariah. In addition, it is also to determine what variables have the most influence on the level of profitability.Method - This study uses secondary data from time series (time series). The research data is sourced from Bank BNI Syariah and BPS from the first quarter of 2011 to the first quarter of 2020. The data analysis method uses the Vector Error Correction Model (VECM) with the Eviews 10 software toolResult - The results showed that the amount of financing has a positive relationship with the profitability of Bank BNI Syariah. Non-performing financing and inflation have a negative relationship with the profitability of Bank BNI Syariah. Meanwhile, based on the variance decomposition, problematic financing is the variable that provides the largest contribution to the profitability of Bank BNI Syariah.Implication - The ratio of non-performing financing should be suppressed as much as possible so as not to reduce profitability.Originality- This study uses the VECM method to determine the factors that affect the profitability of Islamic banks.